Ambivalent Occidentalism in Mochtar Lubis’s Cold War Literature Maut dan Cinta - Muhammad Taufiqurrohman; Sudibyo Sudibyo; Fadlil Munawwar Manshur (Universitas Sanata Dharma, 2025)
This article revisits Maut dan Cinta (1977), a seminal Cold War-era novel by Indonesian author Mochtar Lubis, to examine how the text engages with cultural imperialism in postcolonial Indonesia through its complex portrayal of the Occident. Employing Martin Suryajaya’s “wide-close-deep” methodology—a three-pronged framework for literary analysis—the study situates Lubis’s work within Indonesia’s Cold War cultural politics, highlighting the author’s contested ideological stance. Through the lenses of Occidentalism and cultural imperialism, the analysis reveals Lubis’s profound ambivalence toward Western influence: while critiquing Western hegemony and cautioning against uncritical adoption of Western values, his works simultaneously echo the capitalist Bloc’s anticommunist rhetoric, and his cultural-intellectual networks remain entrenched in Western capital. This paradox deepens with Lubis’s selective embrace of Western liberalism, which coexists with a striking silence on capitalism’s role in perpetuating global inequality. Crucially, his vehement rejection of communist internationalism starkly contrasts with his reluctance to address capitalism’s transnational exploitation of the Global South—a contradiction epitomized by his protagonist Sadeli’s distorted view of the Occident and the characters’ failure to recognize global capitalism’s neocolonial and culturally imperialist dynamics. By unpacking these tensions, the study argues that Lubis’s ambivalence in Maut dan Cinta reflects the broader ideological fissures of postcolonial intellectual resistance during the Cold War, caught between anti-imperialist critique and complicity in hegemonic structures.